MEDIA BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) DALAM PEMBELAJARAN SAINS PADA ANAK USIA DINI - Ice Karlina Leriyono; NINA KURNIAH; MONA ARDINA (Universitas Bengkulu, 2018)
The purpose of this research was to develop learning media based on Information and Communication Technology (ICT) in learning primary school science in the form of powerpoint with fruit theme. The desig of this research used by Research and Development (R & D) were adapted from the Borg and Gall models. The subjects of this research consisted of a teacher and ten A group children for small group trials, while for large group trials in two teachers with two classes with nine each. To made effective media there were some things to gave attention such as the text introduced to the child begins with lowercase instead of capital letters, written spelling made in the media raised by letter because in the early class children the introduction of words easier to do with spelling alphabet. Then the inserted image wasn’t too much and the animation was too big can disturb the focus and concentration of the child on the material displayed. As well as the color of writing, the size of the writing should be enlarged with a bright color so didn’t make difficult for children to spell the text presented. In addition, the selection of videos tailored to the material and media objectives, so that the results of this research was ICT-based media in the form of powerpoint appropriate to use teachers in science learning for childhood.Keywords: ICT-based media, Science lessons, Early childhood